Shoot Induction of Dendrobium lasianthera J.J.Smith with Several Types of Cytokinins through In Vitro Culture - Naura Muthiah Arli; Zozy Aneloi Noli (Jurnal Penelitian Pendidikan IPA, 2024)
Dendrobium lasianthera (Orchidaceae) is one of the potential plants as ornamental plants because it has beautiful and long-lasting flowers. Propagation of orchid plants through in vitro culture technique has been widely done to meet market demand. One of the supporting factors in plant propagation through in vitro culture techniques is growth regulators. Cytokinin is one of the growth regulators commonly used in plant propagation, including orchids. The study aims to determine the effect of several cytokinins and find the best type for shoot induction of Dendrobium lasianthera. The method used a Completely Randomized Design (CRD) with 4 treatments and 6 replications with several types of cytokinis (control; BAP 1.2 mg/L, Kinetin 2 mg/L, and Thidiazuron 1 mg/L) in Murashige & Skoog (MS) media. The results showed that several cytokinins significantly affected the number of shoots, time of shoot appearance, and shoot length of D. lasianthera. Thidiazuron was the best cytokinin for in vitro shoot induction of D. lasianthera